2009
DOI: 10.1111/j.1099-0860.2008.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I Need Help on Mondays, It’s Not My Day. The Other Days, I’m OK’.—Perspectives of Disabled Children on Inclusive Education

Abstract: This article examines the experience of inclusive education from the perspective of disabled children. We worked with the observations of, and interviews with, 15 children, aged 5–17 who go to a mainstream school. The study is set in the context of a 3‐year research project exploring the practice of inclusive education in Flanders. Here, we report on the key findings from the children’s accounts, focusing on what they had to say about themselves, what they think about school, friends, support and their future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…Giangreco (2009, p. 3) cautions that 'the nature of the support [provided to students with disabilities] may be inconsistent with individual goals that are geared toward greater student independence' , which was evident in this case, to the detriment of the young people's inclusion. These findings are consistent with other studies (Broer et al, 2005;De Schauwer et al, 2009;Mortier et al, 2011;Tews & Lupart, 2008), and show that young people with VI feel similarly towards paraprofessionals, as do those with intellectual and other impairments.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Giangreco (2009, p. 3) cautions that 'the nature of the support [provided to students with disabilities] may be inconsistent with individual goals that are geared toward greater student independence' , which was evident in this case, to the detriment of the young people's inclusion. These findings are consistent with other studies (Broer et al, 2005;De Schauwer et al, 2009;Mortier et al, 2011;Tews & Lupart, 2008), and show that young people with VI feel similarly towards paraprofessionals, as do those with intellectual and other impairments.…”
Section: Discussionsupporting
confidence: 95%
“…Students in receipt of paraprofessional support appear to constantly experience feelings of dependence on support personnel, which negatively affected their sense of autonomy (Tews & Lupart, 2008). Furthermore, the studies reported that students often felt controlled by support personnel (Broer et al, 2005;De Schauwer et al, 2009;Mortier et al, 2011;Tews & Lupart, 2008). Students who attended classes accompanied by paraprofessionals continually compared themselves against their peers who did not receive support.…”
Section: Students' Views Of Paraprofessional Supportmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent literature has begun to address this gap (e.g. Connors and Stalker, 2007;De Schauwer et al, 2009;Shah, 2005).…”
Section: Educational 'Inclusion' Sen and Normalisationmentioning
confidence: 99%
“…Entre sus resultados, se señala que "algunos de los factores que inciden en que no se dé una completa atención son: motivación de los docentes, exigencias del colegio y de los padres, falta de evaluación por parte de la institución al proyecto (…)" (Arias et al, 2005: 51). Existen diferentes miradas sobre sus resultados, por una parte, algunos autores defienden sus efectos positivos (Thomas, 1997;De Schauwer et al, 2009), otros enfatizan en las múltiples complejidades en su implementación (Clark et al, 1999;Norwich y Kelly, 2004) o la falta de evidencia sobre esta (Lindsay, 2007;Kelly et al, 2014).…”
Section: Aspectos Clave De La Inclusión Escolarunclassified